The Role of Civic Engagement in Increasing Learning Motivation of Coastal Children - Lathifah Sandra Devi; Ujang Jamaludin; Dinar Sugiana Fitrayadi (Universitas Djuanda, 2020)
The involvement of citizens in participation as an embodiment of a sense of awareness and the desire to contribute will form an activity that can influence and lead to change. The maritime children's school community is a forum for citizens to participate in an activity in order to increase the motivation to learn coastal children. The purpose of the study was to know the role of civic engagement in increasing the motivation to learn coastal children. This research was conducted at the School of Marine Children located in the village of Tanjung Kait, District Mauk, Tangerang Regency using a qualitative approach. Data collection is how to interview, study documentation, and observation by analyzing data using Miles and Haberrman models. The results of the study state that the role of participant or citizen involvement in the learning process through extrinsic motivation in the form of material and moral rewards. A good and conducive learning environment by providing appropriate facilities and infrastructure, and interesting learning activities by learning while playing to create an innovative learning atmosphere. With this enhancement of children's learning motivation can be done on the involvement of citizens as instructors at the nautical children's school.